2005
DOI: 10.2166/wst.2005.0273
|View full text |Cite
|
Sign up to set email alerts
|

Steroid estrogens in primary and tertiary wastewater treatment plants

Abstract: The concentrations of two natural estrogens (estrone (E1) and Estradiol (E2)) and one synthetic progestin (Ethinylestradiol (EE2)) were measured for different unit operations in an advanced sewage treatment plant and in a large coastal enhanced primary sewage treatment plant. The average influent concentration to both plants was similar: 55 and 53 ng/L for E1 and 22 and 12 ng/L for E2 for the advanced and enhanced primary STPs, respectively. The activated sludge process at the advanced STP removed up to 85% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…So far, the occurrence and removal of estrogens in WTPs have been reported in many studies around the world [3]. As conventional processes in municipal wastewater treatment plants are not able to eliminate estrogens to an ineffective level [4], advanced treatment processes is needed to minimize the discharge of those estrogens. Therefore, the application of flocculation products.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the occurrence and removal of estrogens in WTPs have been reported in many studies around the world [3]. As conventional processes in municipal wastewater treatment plants are not able to eliminate estrogens to an ineffective level [4], advanced treatment processes is needed to minimize the discharge of those estrogens. Therefore, the application of flocculation products.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Consequently, EE2 and E2 have been detected in sewage sludge and biosolids at concentrations ranging from 0.4 to 18 mg kg ¡1 for EE2 and from 0.2 to 49 mg kg ¡1 for E2. [5][6][7][8][9] Antibiotics have also been detected in sewage sludge and biosolids. [10][11] Ciprofloxacin is a fluoroquinolone antibiotic that is commonly administered to humans in treating urinary tract and intestinal infections.…”
Section: Introductionmentioning
confidence: 99%
“…Baronti et al (2000), Johnson and Sumpter (2001), Fujii et al (2002), Andersen et al (2003), Svenson et al (2003), Williams et al (2003) and Braga et al (2005) reported that activated sludge systems can remove 10-95% of estrogens in municipal wastewater. Consequently, there is a need to consider advanced processes, such as membrane bioreactor (MBR), as a viable option for the removal of these compounds.…”
Section: Introductionmentioning
confidence: 99%